2016
DOI: 10.1101/041475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copy number variants in the sheep genome detected using multiple approaches

Abstract: Background: Copy number variants (CNVs) are a type of polymorphism found to underlie phenotypic variation, both in humans and livestock. Most surveys of CNV in livestock have been conducted in the cattle genome, and often utilise only a single approach for the detection of copy number differences. Here we performed a study of CNV in sheep, using multiple methods to identify and characterise copy number changes. Comprehensive information from small pedigrees (trios) was collected using multiple platforms (array… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The CNVRs identi ed in these previous studies were different to some extent, which may have been related to the differences in sheep breeds, sample sizes, CNV detection platforms and CNV calling algorithms used. However, it is noteworthy that the CNVRs identi ed in this study had high overlapping ratios (27.93%-55.46%) with the CNVRs identi ed by Liu et al, Ma et al, Zhu et al, and Ma et al, but had low overlapping ratios (4.39%-12.59%) with the CNVRs detected by Fontanesi et al, and Jenkins et al, [7,11,13,15,16,28]. The four studies with which there were high overlapping ratios all used Chinese indigenous sheep breeds or Chinese cultivated sheep breeds as the study subjects, whereas the two studies with which there were low overlapping ratios used foreign sheep breeds.…”
Section: Discussionsupporting
confidence: 48%
“…The CNVRs identi ed in these previous studies were different to some extent, which may have been related to the differences in sheep breeds, sample sizes, CNV detection platforms and CNV calling algorithms used. However, it is noteworthy that the CNVRs identi ed in this study had high overlapping ratios (27.93%-55.46%) with the CNVRs identi ed by Liu et al, Ma et al, Zhu et al, and Ma et al, but had low overlapping ratios (4.39%-12.59%) with the CNVRs detected by Fontanesi et al, and Jenkins et al, [7,11,13,15,16,28]. The four studies with which there were high overlapping ratios all used Chinese indigenous sheep breeds or Chinese cultivated sheep breeds as the study subjects, whereas the two studies with which there were low overlapping ratios used foreign sheep breeds.…”
Section: Discussionsupporting
confidence: 48%
“…Due to the difference in CNV detection platforms, the quantity of detected CNVs varies widely in different studies. In terms of the CNVs captured by aCGH and SNP chips, the number usually ranges from dozens to hundreds, and the average length is approximately 100-300 kb [28][29][30][31][32]. Using whole genome resequencing, Cheng et al [33] reported that 4301 CNVRs were identi ed in three Chinese breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rice, a recent study of 3010 rice varieties identified thousands of deletions and hundreds of duplications affecting between 100 bp and 1 Mb [47]. Indeed, there are often significant inconsistencies in the results of CNV analyses from different studies within the same species due to differences in sample sizes, breeds used, and methodologies of CNV detection (Box 1) [22,48,49]. This was highlighted in a recent analysis, albeit in a domesticated animal species, which characterized CNVs in European cattle (Bos taurus) populations and compared the results to 18 previous studies [39].…”
Section: Cnvs Are Widespread In Domesticated Speciesmentioning
confidence: 99%